Political Polarization and Selective Exposure of Social Media Users in Indonesia - Denny Januar Ali; Eriyanto Eriyanto (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2021)
This study is intended to answer the question of how political polarization is related to social media users’ posts about Covid-19. The researchers chose health cases related to Covid-19 instead of political issues (e.g. elections) to prove that this political polarization has spread to many areas. The research also wants to see the relationship between this political polarization and selective exposure. Theories applied in this study are polarization, filter bubble, and selective exposure. The study applied two methods: social media network analysis and content analysis. The network analysis included 82,156 posts, while the content analysis was carried out on 4,050 social media accounts. The research outcome proves the occurrence of political polarization. Social media users were divided into two major groups, namely pro-Jokowi and anti-Jokowi. Each group interacted with fellow users who had the same political choices and shared the same message content. Users with certain political choices tend to receive the same information as their political choices, and ignore information from other political parties. Another interesting finding from this study is how this polarization was sharpened by the use of hashtags. Each party (supporters and oppositions of Jokowi) uses hashtags to create solidarity and mobilization from each supporter. Research also proves the validity of the selective exposure and filter bubble hypothesis in the Indonesian context.